A comparative study of ROTEM-EXTEM results obtained from EDTA-treated whole blood samples and Sodium Citrate-treated whole blood samples in healthy volunteers - Du Preez, Marlize (Department of Anaesthesia, 2017)
Background: A number of anticoagulants are available in clinical use to preserve blood samples in liquid form until a suitable time for laboratory testing. Rotational thromboelastography is usually performed on a blood sample that has been anticoagulated with sodium citrate and then recalcified immediately prior to testing. In our institution we have had shortages of citrated Vacutainer® sample tubes. The use of a single in vitro anticoagulant promises to cut costs, simplify laboratory processes as well as limit the amount of blood drawn from patients. This together with the known problems with using citrate as an anticoagulant for viscoelastic testing (VET) prompted us to investigate the suitability of EDTA as anticoagulant for VET. Method: Blood samples from 20 healthy volunteers were divided into citrated and EDTA Vacutainer® tubes. A ROTEM EXTEM® assay was performed on each sample in both groups following the manufacturer's guidelines. Clotting time (CT), clot formation time (CFT), alpha angle (α-angle) and maximum clot firmness (MCF) results were compared. Ionised calcium concentrations were measured on each sample before and after recalcification with CaCl2 to determine if there was a significant difference in post - recalcification ionised calcium concentrations between the groups. Results: The results from the two groups were treated by Bland-Altman analysis. Apart from MCF values there was significant bias between all parameters measured in the two groups. The limits of agreement for all parameters apart from MCF were unacceptable. Conclusion: We found that ROTEM EXTEM® results from EDTA samples were not comparable to or interchangeable with those from citrated samples. The difference in results is not due to differences in ionised calcium concentration levels in the samples post-recalcification as the ionised calcium concentrations in both groups post-recalcification were adequate for coagulation. EDTA samples did show superior consistency in all parameters and may be a suitable alternative for sample preservation for VET if reference ranges can be established.